Actions crossing of the teachers in the space and in the time (Research, Society and Development, 2021)
The goal of this study is to show the reflections of different teachers’ reports in relation to other teachers that were significant in their career choices from beginning years of study to graduation level. Thus, understanding the genesis and the development of the teaching are necessary to learn and to analyze the teacher’s actions in that time. For that, was carried out a half-structured interview with Science and/or Biology Teachers that taught in the years 1970, 1980, 1990, 2000 and 2010.  Two teachers from each indicated period were interviewed. All the 10 teachers that answered the interview are from the Regional Education Center (REC) from Goioere-PR. Following the methodology of the Textual Discursive Analysis proposed by Moraes and Galiazzi (2011), it was possible to understand the influences of the Science and Biology teachers in their professional choices. Also, the teaching practices of the outstanding teachers who left positive and/or negative memories in their students were considered, practices that crossing the time and the space, perpetuating your presence and actions.